Method and system for establishing fetal birth weight estimation model - TIAN YANRAN (2018)
The invention relates to a method and a system for establishing a fetal birth weight estimation model. The method comprises the following steps of collecting the weight information of a sample fetus and the antenatal parameter information related to the weight of the fetus; dividing the antenatal parameter information of the sample fetus into two groups according to the weight information of the sample fetus, performing the significance test on the information to obtain a P value, and obtaining the statistical parameter information of the sample according to the P value; subjecting the statistical parameter information of the sample to the subject working characteristic curve analysis and obtaining the sample sensitive parameter information; performing the regression analysis according tothe weight information and the sensitive parameter information of the sample fetus, and establishing a fetal weight estimation equation to obtain a fetal birth weight estimation model. The establishment method of the estimati